The Dentato-Rubro-Olivary Tract: Clinical Dimension of This Anatomical Pathway - Fadil Khoyratty; Thomas Wilson (Case Reports in Otolaryngology)
Symptomatic palatal tremor is potentially the result of a lesion in the triangle of Guillain-Mollaret (1931) and is associated with hypertrophic olivary degeneration (HOD) which has characteristic MR findings. The triangle is defined by dentate efferents ascending through the superior cerebellar peduncle and crossing in the decussation of the brachium conjunctivum inferior to the red nucleus, to finaliy reach the inferior olivary nucleus (ION) via the central tegmental tract. The triangle is completed by ION decussating efferents terminating on the original dentate nucleus via the inferior cerebellar peduncle. We can demonstrate the anatomy of this anatomical triangle using a clinical case of palatal tremor presenting with bilateral subjective pulsatile tinnitus along with the pathognomonic MR findings previously described. The hyperintense T2 signal in these patients may be permanent, but the hypertrophied olive normally regresses after 4 years. The temporal relationship between the evolution of the histopathology and the development of the palatal tremor remains unknown as does the natural history of the tremor. Botox injection at the level of tensor and levator veli palatini insertion have been used to treat patients with disabling tremor synchronous tinnitus. A lesion involving the triangle can have a quite varied clinical expression.